A chorus rises - Morrow, Bethany C. (Tor Teen, 2021)
After exposing a Siren to the world, teen influencer Naema Bradshaw's life has taken a turn. Vilified by the media, she's forced to leave her home and heads to the Southwest in order to stage a comeback. There, she finds an online community that supports her, and Naema feels like she's getting some of her old life back. But when her new "fans" start attacking other Black girls, she realizes that even the privilege of fame has its limits.